Allergenicity of recombinant Humulus japonicus pollen allergen 1 after combined exposure to ozone and nitrogen dioxide. (March 2018) - Hong, Qiang; Zhou, Shumin; Zhao, Hui; Peng, Jiaxian; Li, Yang; Shang, Yu; Wu, Minghong; Zhang, Wei; Lu, Senlin; Li, Shuijun; Yu, Shen; Wang, Weiqian; et al.
Abstract: Ozone (O3 ) and nitrogen dioxide (NO2 ) are thought to play primary roles in aggravating air pollution-induced health problems. However, the effects of joint O3 /NO2 on the allergenicity of pollen allergens are unclear. Humulus japonicus pollen allergen 1 (Hum j1) is a profilin protein that causes widespread pollinosis in eastern Asia. In order to study the effects of combined O3 /NO2 on the allergenicity of Hum j1, tandem six-histidine peptide tag (His6)-fused recombinant Hum j1 (rHum j1) was expressed in a prokaryotic system and purified through His6 affinity chromatography. The purified rHum j1 was used to immunize SD rats. Rat sera with high titers of IgG and IgE antibodies against rHum j1 were used for allergenicity quantification. The rHum j1 was exposed to O3 /NO2, and changes in allergenicity of the exposed rHum j1 were assayed using the immunized rat antibodies. Tandem LC-MS/LC (liquid chromatography-mass spectrometer/liquid chromatography spectrometer) chromatography and UV and circular dichroism (CD) spectroscopy were used to study the structural changes in rHum j1. Our data demonstrated that a novel disulfide bond between the sulfhydryl groups of two neighboring cysteine molecules was formed after the rHum j1 exposure to joint O3 /NO2, and therefore IgE-binding affinity was increased and the allergenicity was reinforced. Our results provided clues to elucidate the mechanism behind air pollution-induced increase in pollinosis prevalence. Graphical abstract: Highlights: High titers of IgG and IgE antibodies induced by Humulus japonicus pollen allergen 1 (Hum j1) were prepared. Combined O3 /NO2 stabilizes allergens and increases their allergenicity.